DESAKRALISASI PARTAI POLITIK ISLAM PADA AWAL REFORMASI DI INDONESIA - Abdul Rahman (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: This study aims to determine (1) the emergence of Islamic parties at the beginning of the reformation (2) the relationship between the desacralization of Islamic parties and the defeat of Islamic parties. The research method applied is the historical method. The results showed that (1) the emergence of so many Islamic parties at the beginning of the reformation was one of the impacts of President B.J Habibie's policy which opened the faucet of democracy by providing opportunities for all citizens of the Republic of Indonesia to form associations and gather through political parties. (2) The presence of an Islamic political party in the 1999 election contestation did not get the majority support from the public so that it failed to emerge as the main winner. The failure of Islamic parties to gain popular support cannot be separated from Nurcholish Madjid's idea of the desacralization of Islamic parties through the jargon of Islam yes, Islamic party no. In addition, the failure of Islamic parties to gain popular support, because the number of Islamic parties is so large that the voter's voice from among Muslims is divided, and Islamic parties are unable to compete with nationalist parties both in terms of financial and work programs offered to voters.Abstrak: Penelitian ini bertujuan untuk mengetahui (1) kemunculan partai Islam pada awal reformasi (2) keterkaitan antara desakralisasi partai Islam dengan kekalahan partai Islam. Metode penelitian yang diterapkan ialah metode historis. Hasil penelitian menunjukkan bahwa (1) kemunculan partai Islam yang begitu banyak pada awal reformasi merupakan salah satu dampak dari kebijakan Presiden B.J Habibie yang membuka keran demokrasi dengan memberikan kesempatan kepada segenap warga negara Republik Indonesia untuk berserikata dan berkumpul melalui jalur partai politik. (2) Kehadiran partai politik Islam dalam kontestasi pemilu 1999 tidak mendapat dukungan mayoritas dari masyarakat sehingga gagal tampil sebagai pemenang utama. Kegagalan partai Islam memperoleh dukungan rakyat tidak dapat dilepaskan dari gagasan Nurcholish Madjid tentang desakralisasi partai Islam melalui jargonnya Islam yes, partai Islam no. Selain itu, kegagalan partai Islam meraih dukungan rakyat, karena jumlah partai Islam sangat banyak sehingga suara pemilih dari kalangan Islam terbagi-bagi, dan partai Islam kalah bersaing dengan partai nasionalis baik dari segi finansial maupun program kerja yang ditawarkan kepada pemilih